Knowledge, Attitude, and Practice of Medical Staff Towards Metabolic Syndrome in Schizophrenia in Chinese Hospitals: A Cross-Sectional Study - Wang Y; Yu X; Chen H; Tang C; Zhang N (Journal of Multidisciplinary Healthcare)
Yuejia Wang,1,2 Xuefen Yu,3,4 Haiqin Chen,2 Chunxia Tang,2 Na Zhang5 1Zhejiang University School of Medicine, Hangzhou, Zhejiang, 310000, People’s Republic of China; 2Nursing Department of Huzhou Third Municipal Hospital, Huzhou, Zhejiang, 313000, People’s Republic of China; 3Stomatology Hospital, School of Stomatology, Zhejiang University School of Medicine, Zhejiang Provincial Clinical Research Center for Oral Diseases, Hangzhou, 310000, People’s Republic of China; 4Key Laboratory of Oral Biomedical Research of Zhejiang Province, Cancer Center of Zhejiang University, Engineering Research Center of Oral Biomaterials and Devices of Zhejiang Province, Hangzhou, 310000, People’s Republic of China; 5Psychiatry Department of Huzhou Third Municipal Hospital, Huzhou, Zhejiang, 313000, People’s Republic of ChinaCorrespondence: Xuefen Yu, Email yuxf@zju.edu.cnBackground: This study aimed to investigate the knowledge, attitude, and practice (KAP) of medical staff regarding metabolic syndrome in schizophrenia in Chinese hospitals, emphasizing implications for improving clinical management.Methods: This multicenter, cross-sectional study enrolled medical staff in 5 hospitals between March 2024 and April 2024. A self-administered questionnaire was developed to collect the demographic information and KAP scores of the participants.Results: A total of 359 valid questionnaires were analyzed, with 280 respondents (77.99%) being female and 298 (83.01%) employed in public tertiary hospitals. Mean scores for knowledge, attitude, and practice were 30.93± 7.45, 28.81± 3.60, and 22.50± 5.11, respectively. The proportion of participants achieving good levels of knowledge, attitude, and practice (defined as scores ≥ 60% of the maximum score) was 75.77%, 99.72%, and 88.58%, respectively. Multivariate logistic regression identified several factors independently associated with practice: higher knowledge scores (OR = 1.16), positive attitude scores (OR = 1.09), being female (OR = 2.64), having ≥ 16 years of experience (OR = 3.24), and previous experience in managing patients with metabolic syndrome in schizophrenia (OR = 0.50). Approximately 64.9% of participants had experience treating patients with schizophrenia and metabolic syndrome, and this experience was significantly associated with higher practice scores. Structural equation model analysis revealed that knowledge influenced attitude (β = 0.10), attitude influenced practice (β = 0.82), and knowledge directly influenced practice (β = 0.50).Conclusion: Medical staff possess adequate knowledge, positive attitude, and proactive practice concerning metabolic syndrome in schizophrenia. Although the overall level of KAP was good, there is still room for further improvement. The findings suggest targeted interventions, such as continuous education programs and training tailored for Chinese medical staff, could enhance their proactive practices in managing metabolic syndrome in schizophrenia patients.Keywords: knowledge, attitude, practice, medical staff, schizophrenia, metabolic syndrome